2007
DOI: 10.1128/jvi.00997-06
|View full text |Cite
|
Sign up to set email alerts
|

Deficient Major Histocompatibility Complex-Linked Innate Murine Cytomegalovirus Immunity in MA/My.L-H2bMice and Viral Downregulation of H-2kClass I Proteins

Abstract: NK cells are key effectors of innate immunity and host survival during cytomegalovirus (CMV) infection. Innate murine CMV (MCMV) resistance in MA/My mice requires Ly49H/m157-independent H-2k-linked NK cell control. Here we show that replacement of MA/My H-2k with C57L H-2b susceptibility genes led to a remarkable loss of innate virus immunity, though NK gamma interferon was induced in H-2b and H-2k strains shortly after infection. Thus, H-2b genes expressed in C57L or MA/My.L-H2b are sufficient in alerting NK … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 39 publications
(44 reference statements)
4
59
0
Order By: Relevance
“…Although the molecular nature of target recognition remains unknown, it is likely that the recognition of H-2D k molecules depends on the viral peptide. These conclusions are corroborated by Brown and colleagues [65]. Altogether, by its specificity for MHC class I allele and viral protein, Ly49P represents another highly specific mechanism of NK cell-mediated control.…”
Section: Interference With Activating Ly49 Nk Cell Receptorsmentioning
confidence: 59%
“…Although the molecular nature of target recognition remains unknown, it is likely that the recognition of H-2D k molecules depends on the viral peptide. These conclusions are corroborated by Brown and colleagues [65]. Altogether, by its specificity for MHC class I allele and viral protein, Ly49P represents another highly specific mechanism of NK cell-mediated control.…”
Section: Interference With Activating Ly49 Nk Cell Receptorsmentioning
confidence: 59%
“…Recent studies by Belanger et al (15) have shown that NOD mice possess a Ly49H activation receptor, but sequence differences from Ly49H B6 result in the failure to control MCMV infection. The evolutionary pressures driving the emergence of activating receptors from inhibitory Ly49 homologues may be due to interactions with more conserved molecules from other pathogens or to MHC class I molecules altered by virus infection, such as is the case for the recognition of H-2D k by the Ly49P activating receptor from MA/My mice (53)(54)(55), where the recognition of H-2D k is dependent on the expression of the MCMV-encoded m04 molecule (56). B6 mice are generally termed "resistant" (Cmv1 r ), but this is true only in the context of m157…”
Section: B6mentioning
confidence: 99%
“…Congenic and transgenic mice were genotyped as described previously using MHC genetic markers 17Mit16, 17Uva12, 17Uva17, 17Uva03,19 Virus studies and in vivo resistance assays Salivary gland stock virus (SGV) was prepared and titered on NIH3T3 monolayers as described. 15 Experimental mice (8-12 weeks) were infected intraperitoneally with 10 4 PFU MCMV, unless indicated otherwise. MCMV genomes in spleen samples were measured using quantitative real-time PCR as described.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15] Classic genetics studies to examine MA/My virus resistance mapped genes to the MHC I D region on chromosome 17 and the NK gene complex (NKC) on chromosome 6. [15][16][17][18] Recently, we identified MHC I D k as a critical genetic factor, 19 and further demonstrated a requisite role of licensed Ly49G2 ϩ NK cells needed in MCMV resistance. 18,19 Consistent with a requirement for NK stimulatory signals, Ly49P has been shown to bind MHC I D k on infected cells displaying MCMV glycoprotein gp34.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation